Pengaruh Kapabilitas terhadap Keunggulan Kompetitif dan Dampaknya terhadap Kinerja Perusahaan pada PT Adi Cipta, Makassar - Budiastuti, Dyah; Versia, Versia (Binus Business Review, 2011)
As a company which implements differentiation strategy, PT. Adi Cipta has achieved competitive advantage in using capabilities through implementing organization culture and quality management. But, for about last 5 years, the companyâs performance seems to be stagnant and having no significant improvement. This research aims to analyze the effect of capability, which is Organization Culture and Quality Management, towards the Competitive Advantage and its effect to the companyâs performance. Data are taken from observation result, questionnaire, and interview with companyâs holder and the decision maker, which then be analyzed with regression method. The research result shows that Organization Culture and Quality Management affect on Competitive Advantage, which affects to the companyâs performance.Â